Clinical evaluation of a two-dimensional liquid-filled ion chamber detector array for verification of high modulation small fields in radiotherapy - Miljenko Markovic; Ganesh Narayanasamy; Sotirios Stathakis; Panayiotis Mavroidis; Ines-Ana Jurkovic; Daniel Saenz; Niko Papanikolaou (Journal of Medical Physics, 2019)
Introduction: Clinical evaluation of a two-dimensional (2D) liquid-filled ion chamber detector array used in the verification of highly modulated small beams of stereotactic body radiation therapy (SBRT) has been conducted. Materials and Methods: Measurements with the Octavius 1000 SRS (PTW, Freiburg, Germany) detector with 977 liquid-filled ion chambers were compared against EDR2 film and PTW Octavius Seven29. The performance of detector array has been evaluated on ten SBRT patient plans. Dose profiles of individual and composite fields' calculated using Pinnacle3 treatment planning system were compared against measurements with Octavius 1000 SRS detector array, EDR2 film, and Octavius Seven29 detector. Gamma index and profile comparison were used in the evaluation and assessment of the detector's performance. Results: The Gamma index measurements show agreement between Pinnacle3 computations and Octavius 1000 SRS array, PTW Octavius Seven29, and EDR2 film for >90% of the points using 2%, 2 mm tolerance criteria. Profiles obtained with the Octavius 1000 SRS were in agreement with the EDR2 film profiles, demonstrating the detector's superior sampling rate. Conclusions: The Octavius 1000 SRS is a dosimetrically accurate device to perform quality assurance checks in SBRT treatments. The broad range of measurements performed in this study quantified the dosimetric accuracy of Octavius 1000 SRS detector in the clinical setup of the small fields in radiotherapy.